Estimativa da poluição emitida pelos ônibus das linhas troncais da cidade de Uberlândia, MG - Silva, Melissa Mariana Ferreira (2016)
The transport of people and goods contributes to the deterioration of the environment in urban areas because of the generation of pollution, such as, air, noise, soil, water or visual degradation. The heavy vehicles that use diesel as fuel are mainly responsible for the emission of nitrogen oxides (NOx) and particulate matter (PM), contributing to participation of the transport sector in air pollution. In addition, there is emission of Greenhouse Gas (GHG) whose main component is carbon dioxide (CO2). In most major cities, public transportation is often considered as a less polluting alternative compared to the private vehicle, in view of the potential to reduce, per passenger, the emissions of GHG and air pollutants. The study area was the city of Uberlândia and the objects of study were the trunk lines of the Sistema Integrado de Transporte (SIT). The emissions of NOx, PM and CO2 were estimated through the bottom-up approach which used the route of each bus line and also fuel consumption obtained through simulation from the TSIS software. The software has some result limitations, there are no report about the emission of pollutants by bus, and it is not able to change specifications for the fuel used by the fleet. The results obtained through calculations of pollutants and GHG emission by the bottom-up approach show that the emission is higher when using fuel comsuption obtained in simulation than using distance. For the results considering fuel and distance there was a reduction in emissions comparing ethanol and diesel.